2017
DOI: 10.1016/j.surfcoat.2017.01.051
|View full text |Cite
|
Sign up to set email alerts
|

In vitro corrosion behavior and cytocompatibility of pure Fe implanted with Ta

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Ghorbani et al [11] reported that Ta film can strongly enhance the corrosion resistance of the 316L stainless steel in Ringer’s solution. Wang et al [12] suggested that the Ta ion implantation is an effective method to improve the cytocompatibility of pure Fe for biomedical applications and only the Ta ion dosage reaching a critical value can significantly increase corrosion resistance in the solution containing SO 4 2− . Moreover, Wei et al [13] coated Ta alloy on the surface of pure titanium and found that the Ta coating shows excellent corrosion resistance in different concentrations of sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Ghorbani et al [11] reported that Ta film can strongly enhance the corrosion resistance of the 316L stainless steel in Ringer’s solution. Wang et al [12] suggested that the Ta ion implantation is an effective method to improve the cytocompatibility of pure Fe for biomedical applications and only the Ta ion dosage reaching a critical value can significantly increase corrosion resistance in the solution containing SO 4 2− . Moreover, Wei et al [13] coated Ta alloy on the surface of pure titanium and found that the Ta coating shows excellent corrosion resistance in different concentrations of sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the higher I corr value of the uncoated sample, which was 1050E-06 A/cm 2 , and lowest I corr value of HA-30Ta further validated that this coating had the highest corrosion resistance. 53 The micro-cracks and micro-pores (Figure 5(b)) present at the Ta coating could be the reason for its lower E corr and higher I corr values as compared to the HA coating. The structural imperfections such as cracks/pores in a coating facilitate corrosion under the coating or on the surface of the substrate which leads to leaching of ions resulting in lower corrosion resistance.…”
Section: Electrochemical Investigationmentioning
confidence: 99%
“…Ta has excellent biocompatibility and corrosion resistance, has been used in pacemaker electrodes, suture wire, cranioplasty plates, radiopaque markers, foil and mesh for nerve repair since the 1940s [ 5 ]. In addition, Ta has been used as single or composite coating material to modify the biological and mechanical properties of pure titanium(Ti) [ 6 , 7 , 8 ], Ti alloy (Ti6Al4V) [ 9 ], polyetheretherketone (PEEK) [ 10 ], cobalt-chromium (CoCr) alloy [ 11 , 12 ], magnesium-based alloy [ 13 ], pure Fe [ 14 ] and 316 L stainless steel [ 15 ]. Recently, the advent of Ti-Ta alloy with different Ta element contents indicates a novel means to fabricate implants for bone defect restoration with improved mechanical strength, and satisfactory elastic modulus and biological properties, compared to pure Ti and Ti alloy [ 2 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%